Eating disorders and related stigma: analysis among a population of Italian nursing students - Lupo, Roberto; Zaminga, Melania; Carriero, Maria Chiara; Santoro, Pietro; Artioli, Giovanna; Calabrò, Antonino; Ilari, Federica; Benedetto, Angelo; Caslini, Manuela; Clerici, Massimo; Conte, Luana; Carvello, Maicol (Acta Biomedica Atenei Parmensis, 2020)
According to the World Health Organization, eating disorders are a constantly growing public health problem in industrialized countries with an important stigmatizing impact. The study investigates stigmatizing beliefs and attitudes towards Anorexia nervosa (AN) and Bulimia nervosa (BN). Materials and Methods: From October 2018 to November 2019, an online survey was conducted for students of the Degree Courses in Nursing of 2 Italian university centres, using the Italian version of the SAB-BN-ITA, adapted for AN. Results: The sample consists of 517 nursing students, aged between 20 and 23. Male subjects presented higher scores, relative to stigma, both for BN (F =17.5, p